التغيير في معنى المفرد والجمع في القرآن الكريم / Changes in Lexical Meaning of Singular and Plural Words in the Quran - Achmad Abubakar; Baso Pallawagau; M. Taufiq Hidayat Pabbajah (Diwan : Jurnal Bahasa dan Sastra Arab, 2021)
حاولت هذه الدراسة  الكشف عن أسرار استعمال المفرد والجمع في غير معناهما الأصلي في القرآن الكريم، وتتكون قضية هذه الدراسة مجيئ استعمال المفرد والجمع في غير معناهما الأصلي في القرآن الكريم،  والأسرار البلاغية في مجيء المفرد والجمع خارجاً عن معناهما الأصلي في القرآن الكريم وأمّا نوع البحث المستخدم في هذه الدراسة فهو البحث الوصفي النوعي وطريقة جمع البيانات من خلال الدراسة التوثيقية لأنها من ضمن البحوث المكتبية، وتحليل البيانات عن طريقة تحليل فني بلاغي على أساس المنطق الاستقرائي. ونتيجة البحث تشير إلى مجيئ استعمال المفرد والجمع في غير معناهما الأصلي في عدة آيات قرآنية؛ لأن التنوع في استعمال المفرد والجمع يؤدي وظائف أساسية في الخطاب القرآني. الأسرار البلاغية أو الدلالات البلاغية في استعمال الجمع عن المثنى والمفرد تأتي للتعميم، والمبالغة، والتكثير والتعظيم واستعمال المفرد عن الجمع يفيد التقليل والتصغير والتحقير والتوبيخ،  وقد يفيد المبالغة والإيجاز ورعاية الفاصلة. والمستفاد من هذه الدراسة نلاحظ أن القرآن الكريم يتوجه بالمتلقي إلى التأثير السريع والمباشر، وهذا منسجم مع الفكرة الإنسانية التي يخاطبها ليخدم الهدف من تنزيله من عند رب كريم رؤوف بعباده يهدف إلى هدايتهم للإيمان والتصديق بأقصر الطرق. الكلمات المفتاحية: استعمال الجمع، استعمال المفرد، الأسرار البلاغيةAbstract:This study aims to uncover the wisdom of using singular (mufrad) and plural (jamak) words that violate its original meaning. The research problem consists of two questions: what are the use of singular and plural words that violate the original meaning of the Qur'an? What is the wisdom and secret behind the use of singular and plural words that violate its original meaning in the Qur'an? The type of research is qualitative descriptive, the data collection method is library research and the data analysis used language arts (balaqhah) analysis. The results show that the use of singular and plural words that violate its original meaning is found in the Qur'anic clauses. The variety use of singular and plural is a fundamental function of the Quranic language. The wisdoms and connotations balaqhah, the use of plural mean mutsanna' (two) and singular denote common, exaggerated (hyperbola), many, and admirable meanings, whereas the use of a single word meaning plural indicates little, contempt, ostracize, humiliation, ridicule or criticisms and sometimes indicate excessive, concise and adaptable meaning. The implication of this study is that the Qur'an has a direct effect on its readers and listeners. This is in line with the human mind as the target, to implement the purpose of the Qur'an revealed by Allah SWT, to give guidance to people so they can quickly believe.